2023
DOI: 10.1037/per0000572
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adolescent identity treatment (AIT) versus DBT-a for the treatment of adolescent borderline personality disorder.

Abstract: Borderline personality disorder (BPD) is among the most severe mental health problems with long-lasting deterioration of functioning. According to a Cochrane review, evidence for methods focused on treatment for adolescent BPD patients is very limited. Aims of the study were to demonstrate the noninferiority of adolescent identity treatment (AIT) compared with dialectical behavior therapy for adolescents (DBT-A), and that intensive early treatment of BPD leads to significant improvement of psychosocial and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For example, Cohen et al reported that the onset of personality disorders emerges early in adolescence (13). The abovementioned results converged to indicated that some characteristics of adolescence might facilitate the onset of personality disorder (14, 15); specifically, these studies indicated that BPD may have predisposing features which facilitate the development of personality disorders (6, [10][11][12][13][14][15]. Some studies recommend that for adolescents with BPD, early diagnosis and intervention are ideal (3,(16)(17)(18) and provide optimal outcomes (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Cohen et al reported that the onset of personality disorders emerges early in adolescence (13). The abovementioned results converged to indicated that some characteristics of adolescence might facilitate the onset of personality disorder (14, 15); specifically, these studies indicated that BPD may have predisposing features which facilitate the development of personality disorders (6, [10][11][12][13][14][15]. Some studies recommend that for adolescents with BPD, early diagnosis and intervention are ideal (3,(16)(17)(18) and provide optimal outcomes (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 93%
“…Although debated, some studies suggest that the diagnosis of personality disorders in childhood or adolescence, should be avoided and personality disorders must not be diagnosed in adolescence owing to continued personality maturation and high developmental variability (3,4). More notably, many studies proposed that adolescence is a pivotal period in the development of personality disorder (5)(6)(7)(8)(9)(10)(11)(12). For example, Cohen et al reported that the onset of personality disorders emerges early in adolescence (13).…”
Section: Introductionmentioning
confidence: 99%
“…It is a sad fact that the accumulated evidence indicating that there are effective treatments for young people with PD (Chanen, Nicol, Betts, & Thompson, 2020) and that good outcomes are possible (Alvarez‐Tomás et al., 2017; Balaratnasingam & Janca, 2020; Buerger et al., 2019; Schmeck et al., 2022; Temes & Zanarini, 2018) has not changed routine clinical practice in many jurisdictions around the globe. This appears to be further evidence of the hostile clinical cultures, referred to above.…”
Section: Assertion: “In Reality the Label “Personality Disorder” Stic...mentioning
confidence: 99%
“…Our research group has studied the effectiveness of Adolescent Identity Treatment (AIT) and Dialectic Behaviour Therapy in adolescent patients with BPD. The result of this study showed that both these treatments are effective at improving psychosocial functioning and personality functioning in these patients [ 20 ]. In the same project [ 21 ], we have also studied ruptures and resolutions occurring in the psychotherapy with AIT.…”
Section: Introductionmentioning
confidence: 99%
“…Confrontation ruptures seemed to have a stronger impact than withdrawal ruptures [ 22 ]. A major limitation of the study by Schenk et al [ 22 ] was that it only contained 10 fully analysed psychotherapies while our total sample amounted to 23 cases [ 20 ]. This was due to a lack of 3RS trained personnel since the involved PhD and master students finished their projects.…”
Section: Introductionmentioning
confidence: 99%